PENINGKATAN KAPASISTAS GURU DALAM MENGIMPLEMENTASIKAN SOAL SKOLASTIK UTBK KEDALAM SOAL MATA PELAJARAN DI SMA NEGERI 1 BELINYU - Prayanti, Baiq Desy Aniska; Kustiawan, Elyas; Sulistiana, Ineu; Dalimunthe, Desy Yuliana; Fahria, Izma; Amelia, Ririn; Humairah, Reni; Afrizal, Aidil Adrianda (Jurnal Abdi Insani, 2024)
Since 2019, the Computer-Based Written Test (UTBK) has been used as a system for university entrance exams. The TPS (scholastic potential test) and Literacy Test are two slightly different test forms that have been utilized in UTBK from 2023. The sole public senior high school in the Belinyu subdistrict is SMA Negeri 1 Belinyu. Less than 30% of pupils get admitted to state colleges, according to data from 2023. Therefore, the purpose of this service is to tell the teachers of SMA Negeri 1 Belinyu about UTBK and to train them in creating subject questions for the Scholastic test at UTBK. The method of activity carried out in the form of a preparatory stage in the form of observation, theme determination, and partner preparation followed by the implementation stage in the form of preparation of UTBK material and scholastic tests, exposure and evaluation. According to the service's results, 95% of participants believe that their comprehension of UTBK scholastic questions is improving, and they are hopeful that students will find it simpler to handle UTBK questions if scholastic questions are applied to the subject matter. The purpose of this service project is to help the teachers at SMA Negeri 1 Belinyu better comprehend the UTBK academic questions that incoming college students would encounter.